Effect of a Dementia Care Class on Knowledge of Community-Based Dementia Care among Informal Caregivers: A Pre-Experimental Study - Novi Tiara; Muhamad Jauhar; Diana Tri Lestari; Ashri Maulida Rahmawati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background. Dementia is developing rapidly, marked by the increasing prevalence of dementia in the world every year, in line with the growing number of the elderly population. Dementia causes dependence, reduced quality of life, and even disability. It is necessary to prevent and treat dementia by empowering informal caregivers. Objectives.This study aimed to determine the effect of a dementia care class on knowledge of community-based dementia care. Methods. A pre-experimental pretest–posttest design with a control group was employed. This research was conducted in the Work Area of the Kaliwungu and Dawe Health Centers, Kudus Regency. A sample of 24 informal caregivers for each intervention and control group was taken using purposive sampling. The research instrument used the Alzheimer's Disease Knowledge Scale (ADKS). The intervention dementia care class was conducted in 4 sessions on two days with a duration of 45-60 minutes per session. Wilcoxon and Man Whitney were used for data analysis. Results. The results showed a statistically significant increase in knowledge scores among informal caregivers in the intervention group compared to the control group with p-value = 0.001 (p <0.05). Conclusion. Dementia Care Class improves knowledge of informal caregiver. These learning models and media can be integrated into elderly posyandu and elderly health programs in healthcare facilities in community-based dementia management.